Pemanfaatan Media Sosial Tiktok sebagai Media Dakwah Ustadz Agam dalam Meningkatkan Nilai-Nilai Islam Remaja Milenial - Salsabila, Adinda; Kholil, Syukur (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
This study aims to understand the use of TikTok social media as a medium for Ustadz Agam's preaching in enhancing Islamic values among millennial youth. This research uses a descriptive qualitative method with a content analysis approach. The research data is sourced from the TikTok account @hyung_Agam and relevant literature. The research data was analyzed through data reduction, data presentation, and conclusion drawing. The results of this study indicate that Ustadz Agam successfully utilizes TikTok as an effective preaching platform, especially for the millennial generation who are very familiar with information technology. By using casual and relatable language, as well as presenting practical and interactive content, Ustadz Agam is able to convey religious messages relevant to the daily lives of teenagers and young adults. His methods include inspirational stories, direct dialogue with followers, and the presentation of current topics, which not only attract attention but also influence the values and actions of his followers. Despite facing challenges in maintaining online consistency, Ustadz Agam's preaching on TikTok demonstrates that a modern approach integrating technology and emotional narratives can significantly enhance the understanding and acceptance of Islamic teachings among millennials